2019
DOI: 10.1186/s13741-019-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

A significant proportion of venous thromboembolism events in general surgical patients occurs after discharge: analysis of the ACS-NSQIP Essentials database

Abstract: BackgroundVenous thromboembolism (VTE) is a major cause of morbidity and mortality in general surgical patients.MethodsThe ACS-NSQIP database was queried and VTE data were collected and analyzed to assess the incidence of VTE at a 500-bed, non-profit, teaching, inner city, community hospital and similar peer institutions from January 1, 2006 to December 31, 2011.ResultsPost-discharge VTE events accounted for 40% of all VTE events within 30 days of discharge. Data show a significant proportion of post-discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Venous thromboembolism (VTE) is a complex multifactorial clinical entity associated with significant morbidity and mortality and can present either as deep venous thrombosis (DVT) and/or concomitant pulmonary embolism (PE) [ 32 ]. VTE in malignancies is multifactorial—it can be cancer-related, as well as individual-related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thromboembolism (VTE) is a complex multifactorial clinical entity associated with significant morbidity and mortality and can present either as deep venous thrombosis (DVT) and/or concomitant pulmonary embolism (PE) [ 32 ]. VTE in malignancies is multifactorial—it can be cancer-related, as well as individual-related.…”
Section: Discussionmentioning
confidence: 99%
“…VTE does have a considerable impact on morbidity, mortality, and economic cost, and has led to the development of VTE risk stratification tools such as the Caprini risk assessment [ 32 ]. In addition to VTE risks associated with major surgical procedures and underlying malignancy, the American Heart Association (AHA) has identified additional factors including prior VTE, age, obesity, immobility, and family history.…”
Section: Discussionmentioning
confidence: 99%
“…13 ACCP 2012 guidelines also recommended pharmacologic prophylaxis for 4 weeks with LMWH for patients at high risk for VTE undergoing abdominal or pelvic surgery for cancer who are not otherwise at high risk for major bleeding (Grade 1B) 6,13 Our study showed that 49.9% of VTE complications occurred after discharge from initial hospitalization, consistent with other studies. 14,15 Extended thromboprophylaxis could be more broadly applied with a better determination of an individual’s risk, which our model provides. A prospective, observational study in 2373 patients undergoing cancer surgery demonstrated that VTE was the most common cause of mortality, responsible for 46.3% of postoperative deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) representing the third most common cause of hospital-related deaths in the United States [1][2][3][4][5][6] and vary across surgical specialties. [7][8][9][10][11][12][13][14][15][16][17] In otolaryngology (ORL) patients, postoperative VTE rates from 0% to 2%, [18][19][20][21][22][23][24][25] with more recent studies reporting rates of 0.02% to 1.3% that varies with the type of ORL procedure performed. [25][26][27] VTE in ORL patients most commonly occur after hospital discharge, [28][29][30][31] with reported post-discharge VTE rates from 0.2% to 7.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) representing the third most common cause of hospital‐related deaths in the United States 1–6 and vary across surgical specialties 7–17 . In otolaryngology (ORL) patients, postoperative VTE rates from 0% to 2%, 18–25 with more recent studies reporting rates of 0.02% to 1.3% that varies with the type of ORL procedure performed 25–27 .…”
Section: Introductionmentioning
confidence: 99%